1984
DOI: 10.1007/bf00541936
|View full text |Cite
|
Sign up to set email alerts
|

Colon motility and colo-anal reflexes in chronic idiopathic constipation. Effects of a novel enterokinetic agent cisapride

Abstract: Motor activity of the colon and reflex behaviour of the anal sphincters in normal subjects and in patients with idiopathic constipation were studied using a novel probe with 5 open-end tips to measure pressures, and 3 balloons for stimulation of the distal colon. Constipation appeared to be associated with an increased threshold of the inhibitory relaxation reflex of the internal anal sphincter (41.7 in normals and 65.7 in patients), and in particular with a blunted sensation of the defaecation urge (51.0 in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
2

Year Published

1985
1985
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 8 publications
3
23
2
Order By: Relevance
“…Evidence for constipation affecting cholinergic mechanisms in the human gut has been described by Paskins et al (1982). In contrast to the findings of Reboa et al (1984), Lee et al (1984) did observe a stimulatory effect of cisapride in non-constipated volunteers. Enhancement of acetylcholine release, which has been shown in the guinea-pig ileum, may not explain the action of cisapride on the human colon in vivo.…”
Section: Methodscontrasting
confidence: 41%
See 3 more Smart Citations
“…Evidence for constipation affecting cholinergic mechanisms in the human gut has been described by Paskins et al (1982). In contrast to the findings of Reboa et al (1984), Lee et al (1984) did observe a stimulatory effect of cisapride in non-constipated volunteers. Enhancement of acetylcholine release, which has been shown in the guinea-pig ileum, may not explain the action of cisapride on the human colon in vivo.…”
Section: Methodscontrasting
confidence: 41%
“…Incubation and superfusion of individual taenia preparations were carried out in the same small volume bath which was fitted with vertical platinum wire electrodes (0.5 mm diameter) to allow electrical field stimulation of the tissue from a constant current stimulator. After 90 min taeniae were exposed to a low then a high dose of cisapride (0.4 and 4.1 ,uM The observations that cisapride stimulates human colonic motility in constipated patients is not unequivocal as the observed change although marked did not reach the accepted level of significance :P = 0.081; Reboa et al, 1984). However the compound did enhance colonic transit in volunteers (Lee et al, 1984).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…These data confirm that cisapride significantly increases the speed of gastric emptying also in normal subjects. The lack of effect on intestinal transit could be explained by the interindividual variation observed in our experiments.Cisapride is a new prokinetic gastrointes tinal agent whose mechanism of action is thought to be via the release of acetylcholine from the myenteric plexus and possibly by blocking serotonin receptors without inter fering with dopaminergic receptors [1,2].Studies with animals and in man have shown cisapride to stimulate gastric empty ing [3][4][5][6] and correct the impaired small bowel transit time [7,8], although clinical research relating to the activity of the drug in normal subjects is very limited [9].Our purpose, therefore, was to simulta neously investigate the effect of cisapride on gastric emptying and on the ileal transit time of a balanced liquid meal in healthy sub jects. …”
mentioning
confidence: 99%